Does Adhesive Resin Application Contribute to Resin Bond Durability on Etched and Silanized Feldspathic Ceramic? - Passos, Sheila Pestana [UNESP]; Valandro, Luiz Felipe; Amaral, Regina [UNESP]; Ozcan, Mutlu; Bottino, Marco Antonio [UNESP]; Kimpara, Estevão Tomomitsu [UNESP] (Quintessence Publishing Co Inc, 2008)
Purpose: To assess the effect of adhesive application and aging on the bond durability of resin cement to etched and silanized feldspathic ceramic.Materials and Methods: Twenty blocks (6.4 x 6.4 x 4.8 mm) of feldspathic ceramic (Vita VM7) were produced. The ceramic surfaces were conditioned with 10% hydrofluoric acid gel for 60 s and silanized. They were then randomly divided into two groups. While half of the group received no adhesive, in the other half, a layer of adhesive (Scotchbond Multi-Purpose Plus) was applied. Each ceramic block was then placed in its silicone mold with the treated surface exposed. The dual-cured resin cement (Variolink 11) was injected into the mold over the treated surface and polymerized. Specimens were sectioned to achieve nontrimmed bar specimens (approximately 12 sticks/block) that were randomly divided into 2 groups: a) non-aged - microtensile bond test immediately after sectioning; b) aged-thermocycling (TC) 12,000 times, 5 degrees C to 55 degrees C, and water storage (50 days). The microtensile bond strength test was performed in a universal testing machine (crosshead speed: 1 mm/min). The failure types were examined using an optical light microscope and SEM. Bond strength results were analyzed using two-way ANOVA and Tukey's test (alpha = 0.05).Results: The adhesive application affected the bond strength results significantly (p = 0.0001) (without adhesive > with adhesive). While aging conditions did not reduce the bond strength in the groups that received no adhesive (20 +/- 5.3 MPa non-aged and 21.5 +/- 5.6 aged) (p = 0.1698), it significantly affected the bond strength results of the group with adhesive application (18 +/- 4.4 MPa to 14.4 +/- 4.7 MPa) (p < 0.001). All groups showed mainly mixed type of failures between the ceramic and the resin cement (81% to 100%). The group in which no adhesive was applied presented a higher incidence of cohesive failure of ceramic after aging (18%) than those of the other groups.Conclusion: The use of adhesive did not improve resin cement adhesion to the etched and silanized feldspathic ceramic after long-term thermocycling and water storage.
Keywords: acid etching; bond durability; glass ceramic; microtensile test; resin cement